Finance for non-finance executives - Singal, Anurag (Finance and financial management collection., 2020)
This book introduces you to the key concepts of finance so you can contribute to the success of your business. It will help you understand the language used by accountants and how financial statements fit together. Furthermore, you will understand how to use ratio analysis to get a sense of the company's performance. In addition, you will learn the concepts of management accounting and various kinds of decisions, including make-or-buy, shutdown, and so on. You will gain an understanding of how to implement Budgeting and Working Capital Management. The exciting part is also the chapter on Investment Appraisal, where you will learn how to evaluate business proposals from a return standpoint.